Situation Analysis of Performance Accountability in Teaching Hospitals Affiliated to Tehran University of Medical Sciences - seyed hesam Seyedin; mohammad mohseni; agha fatemeh Hossaini; Mehdi Gharasi Manshadi; heshmatollah asadi (Tehran University of Medical Sciences, 2015)
Background:  hospital is one of the most key institutions in the modern health care system and accountability is the most essential organizational functions. Accountability strengthens the main factors to responsibility regarding functions by pushing them up. This study aimed at assessing the situation analysis of  performance accountability in teaching hospitals affiliated to Tehran University of Medical Sciences Materials and Methods: This descriptive and analytical study performed at 12 teaching hospitals of Tehran University of Medical Sciences in 2013. Data collection performed by performance accountability checklist. Analysis was done by SPSS software version 19 using descriptive and analytical statistics test (Pearson correlation coefficient). Results: In general, the condition of accountability for hospitalschr('39') performance (Mean =1.5 from 2) measured "good"(moderate to high). Strategic planning dimension achieved the highest score (Mean±SD:1.85±0.21) and Stakeholder Participation had the lowest score (Mean±SD: 1.12±0.46). There was a positive significant correlation between all variables (except Motivation) and performance accountability. Conclusion: Weakness in any part of performance can affect other parts and have negative impact on total hospital performance. Mentioning the current situation of accountability for hospitalschr('39') performance and its importance, reinforcing weak dimensions and addressing deficiencies in  performance accountability should be consider as managerschr('39') top priority.